Phosphoproteomic Analysis Of Mammalian Infective Trypanosoma Brucei Subjected To Heat Shock Suggests Atypical Mechanisms For Thermotolerance - Ooi, Cher-Pheng; Benz, Corinna; Urbaniak, Michael (My University, 2021)
The symptoms of African sleeping sickness, caused by the parasite Trypanosoma brucei, can include periods of fever as high as 41 °C which triggers a heat shock response in the parasite. To capture events involved in sensing and responding to heat shock in the mammalian infective form we have conducted a SILAC-based quantitative proteomic and phosphoproteomic analysis of T. brucei cells treated at 41 °C for 1h. Our analysis identified 193 heat shock responsive phosphorylation sites with an average of 5-fold change in abundance, but only 20 heat shock responsive proteins with average of 1.5-fold change. These data indicate that protein abundance does not rapidly respond (≤1 h) to heat shock, and that the changes observed in phosphorylation site abundance are larger and more widespread. The heat shock responsive phosphorylation sites showed enrichment of RNA binding proteins with putative roles in heat shock response included P-body / stress granules and the eukaryotic translation initiation 4F complex. The ZC3H11-MKT1 complex, which stabilises mRNAs of thermotolerance proteins, appears to represent a key signal integration node in the heat shock response. Significance: We report the first quantitative study of changes in protein and phosphorylation site abundance in response to heat shock in the clinically relevant form of the human parasite Trypanosoma brucei. The identification of heat shock responsive phosphorylation sites on proteins with putative roles in thermotolerance including the ZC3H11-MKT1 complex provides evidence of the role dynamic phosphorylation of RNA binding proteins in co-ordinating heat shock. Temperature changes in the host are a major physiological challenge to parasites and factors conferring tolerance to heat shock constitute overlooked virulence factors. A better understanding of these virulence factors will pave the way for the development of novel drug therapies which selectively target T. brucei.
Keywords: African sleeping sickness; Trypanosoma brucei; phosphoproteomics